Integral super twisting sliding mode control (ISTSMC) application in 1DOF internal mass autonomous underwater glider (AUG) - Maziyah, Mat Noh; Mohd Rizal, Arshad; Rosmiwati, Mohd Mokhtar; Zainah, Md. Zain (Springer Singapore, 2018)
This paper presents the design and implementation of the integral super twisting sliding mode control for the tracking control of a linearized model of longitudinal plane autonomous underwater glider. The performance of the proposed controller is evaluated in terms of chattering reduction in control input for the nominal system as well as the system in the presence of external disturbance. The controller is designed for the gliding path from 45° to 30° downward and upward. The performance of the proposed controller is compared with the quasi sliding mode control (boundary layer), integral sliding control, and super twisting sliding mode control. The simulation results have shown that the proposed controller is able to eliminate the undesired chattering.in control inputs.